1990
DOI: 10.1288/00005537-199003000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Production rate and composition of cerumen: Influence of sex and season

Abstract: The production rate and composition of cerumen have been studied in 11 participants (5 men and 6 women), 25 to 42 years old. The cerumen was obtained in January, May, July, and November to investigate the possible influence of the season. Only the triglyceride content decreased from November to July. Sex was not a factor, which supported the hypothesis that sex hormones play a minor role in the production rate of the lipid component of cerumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
2
15
1
Order By: Relevance
“…This fi nding is comparable to those of Cipirani et al [11] who observed no sex difference in the production of cerumen and Jacobsen [12] who observed that the decline in sebum production as age advances is almost same in males and females. But at the same time in the study conducted by Chiang [13], it was inferred that there are striking sex differences in the production of sebum as infl uenced by hormonal stimuli.…”
Section: Sexsupporting
confidence: 89%
“…This fi nding is comparable to those of Cipirani et al [11] who observed no sex difference in the production of cerumen and Jacobsen [12] who observed that the decline in sebum production as age advances is almost same in males and females. But at the same time in the study conducted by Chiang [13], it was inferred that there are striking sex differences in the production of sebum as infl uenced by hormonal stimuli.…”
Section: Sexsupporting
confidence: 89%
“…This has been attributed to the larger and coarser hairs in the external auditory canal of males. However many studies [8,9,10] did not find any significant difference in the sex incidence of cerumen impaction.…”
Section: Results:-mentioning
confidence: 93%
“…Glandular secretions from the hair in the canal also mix and forms sticky substance known as cerumen. [1,2] The wax produced forms a physiological barrier between the external environment and deep external auditory canal. Chemical composition of wax has also been believed to have antibacterial and antifungal properties, though this is under controversy, as some authors suggest that wax has rich level of nutrients which aid in microbial growth rather than inhibit it.…”
Section: Introductionmentioning
confidence: 99%